Pemodelan Sesar Pasca Gempa Dengan Inversi Data Gravitasi Time Lapse - Muhammad Zuhdi; Muhammad Taufik; Sutrio Sutrio; Syahral Ayub (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2019)
Time lapse or 4D gravity is the development of gravity methods with the fourth dimension is time. This method is characterized by repetitive measurements over a period of time using a high-precision gravity measuring device (gravimeter) which is supported by high accuracy measurement of position. In the case of a fault that triggers an earthquake, layers that have a different density between layers will have the effect of changing the measured value of the gravitational field on the surface. The difference in the value of measured gravity before and after the occurrence of a fault as a result of an earthquake is what gives the value of time lapse gravity. The model of position displacement of the layers before and after the earthquake, provides a model of density between times whose gravitational anomalies can be calculated by forward response. The response of time-lapse forward model (synthetic data) is then optimized to obtain an inversion model. Inversion programming is made using the Mathlab program which is based on the semi-infinite horizontal slab equation. The model parameters that are optimized are horizontal position, depth, and amplitude factor of faulted layers. The program testing on 3 different synthetic data shows that the fastest optimization was obtained in the 7th iteration step. The smallest RMS error from the 3 models was 1.23. 10-5. This inversion program can be applied to time lapse gravity anomalies results of measurements in the field in active fault zones before and after the occurrence of an earthquake